(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Cinema plays a huge role in our youth. They affect people lifestyle. Our generation should pay more attention in small details such as watching films, social network, and mobile phones. Cinema has a great educative value. It can achieve splendid results in the field of expansion of education.